The Effect of Transparency, Accountability, and Subjective Norms on Loyalty and Decisions of Muzakki - Kautsar Riza Salman (Journal of Economics, Business, and Accountancy Ventura, 2022)
This study aims to acquire empirical evidence regarding transparency and accountability on muzakki loyalty through muzakki satisfaction. In addition, this study aims to obtain empirical evidence regarding the effect of transparency and accountability on muzakki decisions through the interest of muzakki. This research is quantitatively conducted where the respondents are 50 zakat payers (muzakki) registered at LAZ Nurul Hayat Tuban. The study uses the Partial Least Square – Structural Equation Model (PLS-SEM) with SmartPLS software. The study results indicate that transparency affects the interest of muzakki in paying zakat, and the interest of muzakki in paying zakat affects the decision of muzakki to pay zakat. In addition, the study’s results also show that accountability affects muzakki satisfaction, and muzakki satisfaction affects muzakki loyalty. The research findings also provide new insights regarding the effect of subjective norms on muzakki’s interest and muzakki’s decision to pay zakat. The first implication of this research is that amil zakat institutions should pay attention to aspects of accountability to stakeholders, especially zakat payers (muzakki). The second implication is that the amil zakat institution should also pay attention to transparency to stakeholders, especially the zakat payers (muzakki). The third implication is that the amil zakat institution should continually educate the public regarding the responsibility to disburse zakat and its benefits for Muslims.